EFFECT OF COMMUNICATION AND CONFLICT ON TEACHERS’ WORKING COMMITMENT IN STATE JUNIOR HIGH SCHOOL AREA OF MUNA REGENCY SOUTHEAST SULAWESI - Asriani, Asriani (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The purpose of this study is to determine the direct effect of communication and conflict on work commitment. The intermediate endogenous variable are communication and conflict, the endogenous variable is work commitment. This research is a quantitative research with survey method at State Junior High School Area of ​​Regency of Muna Southeast Sulawesi. The observational population is the teacher of the State Junior High School Area of ​​Muna Regency Southeast Sulawesi with a total of 393 people using survey method with path analysis used in hypothesis testing. Determination of the sample by using simple random technique was chosen using Slovin formula so that the number of samples to 80 respondents. The results of this study conclude that: (1) there is a positive direct effect of communication on work commitment, (2) that there is a direct negative effect of conflict on work commitment, (3) there is a direct negative effect of communication on conflict. Keyword: communication, conflict and work commitment